Feasibility of microalgal lipid production (for biodiesel) utilising human urine - Tan, Jia Ying (2014)
With fossil fuels depleting, biofuel is emerging as an alternative means of energy in the market. Even though biofuel is a renewable energy, problems arising from competition with food crops on land area may occur. This may result in food shortage. Microalgal biomass production, which does not require the use of arable land, provides a new feasible source to produce biofuel. However, microalgae’s nitrogen and phosphorus demand will increase the fertiliser prices and in turn the food prices. Human urine has been identified in this study to provide the main nutrients required for microalgae cultivation. Urine being 1% of the domestic wastewater volume contributes about 40% of the phosphorus load and 69% of the nitrogen load. Conventional methods to recover phosphorus and nitrogen from urine are struvite precipitation and ammonia stripping. The purpose of this project is to study the feasibility of cultivating microalgae using urine and achieving recovery of nitrogen and phosphorus in urine. When diluted fresh urine of up to 80 times dilution is used as nitrogen and phosphorus feedstock in this study, the cultures achieved up to 87.8% nitrogen recovery and 100% phosphorus recovery. A further scale-up experiment was done with consideration of the anticipated practicality and feasibility in a large-scale setup. The designed expanded sequencing batch culture system has achieved maximum nitrogen and phosphorus utilisation rates of 93.0% and 96.6% respectively in a 1 day cycle. The biomasses produced were compared with control biomasses grown in standard cultivation medium and no inferiority in lipid composition and energy contents were observed. Possible bacteria growth in the culture is identified but the application of photoautotrophic condition can resolve the problem. Human urine is definitely a waste stream that could potentially be reused to provide bulk of the nutrients required for large-scale microalgal cultivations.